HYDROLYTIC WEAKENING OF JADEITE IN UHP JADEITE-QUARTZITES FROM THE DABIE MOUNTAINS, EASTERN CHINA - Su W.; Ye K.; Liu J. (My University, 2006)
Deformed jadeite grains in the UHP jadeite-quartzites from the Dabie Mountains, eastern China show evidence (by transmission electron microscopy, TEM) of plastic deformation: free dislocations, dislocation loops, dislocation networks, dislocation arrays and regularly spaced subgrain boundaries by dislocation walls. Electron energy-loss spectroscopy and TEM studies reveal the existence of water-rich bubbles within dislocations and imply a relationship with water-defect dislocation by water weakening in the jadeites. These observations suggest that the water-rich bubbles are a major weakening effect facilitating plastic deformation of jadeite by dislocation creep. © 2006 The Mineralogical Society.
Keywords: CHINA; DABIE MOUNTAINS; DEFORMATION MECHANISM; EELS; NATURAL JADEITE; TEM; WATER WEAKENING; WATER-RICH BUBBLES